2018
DOI: 10.1159/000490185
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Angelica Sinensis Polysaccharide on Tumor Growth and Iron Metabolism by Regulating Hepcidin in Tumor-Bearing Mice

Abstract: Background/Aims: Iron plays a fundamental role in cell biology and its concentration must be precisely regulated. It is well documented that excess iron burden contributes to the occurrence and progression of cancer. Hepcidin secreted by liver plays an essential role in orchestrating iron metabolism. In the present study, we aimed to investigate the ability of angelica sinensis polysaccharide (ASP) to decrease iron burden in tumor-bearing mice and the mechanism of ASP regulation hepcidin expression. Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 36 publications
0
16
0
1
Order By: Relevance
“…Many natural products have been found to possess many bioactivities, such as anti-tumor effects, anti-oxidant function, and anti-inflammatory activity (Newman and Cragg, 2012;Chen et al, 2016a;Chen et al, 2016b;Ren et al, 2018). Dandelion is a popular Chinese medicinal herb widely grown in lawns, roadsides as well as shores of water ways and often consumed as a vegetable.…”
Section: Introductionmentioning
confidence: 99%
“…Many natural products have been found to possess many bioactivities, such as anti-tumor effects, anti-oxidant function, and anti-inflammatory activity (Newman and Cragg, 2012;Chen et al, 2016a;Chen et al, 2016b;Ren et al, 2018). Dandelion is a popular Chinese medicinal herb widely grown in lawns, roadsides as well as shores of water ways and often consumed as a vegetable.…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript to be reviewed response (MARCO) , iron homeostasis regulation (HAMP) (F Ren et al, 2018), proteoglycans synthesis (ECM1 (H Chen et al, 2011), DCN(Z Horvath et al, 2014)) have been reported to be associated with the progression or prognosis of HCC. Especially, two miRNAs-hsa-miR-106b and hsa-miR-195, which were verified as HCC classifiers in two independent profiles, have been also implicated in regulating HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…6 Additionally, it also could exert its anti-tumor activity by regulating iron metabolism, which might make hepcidin, IL-6, ferritin, transferrin (Tf), transferrin receptor 1 (TfR1), and TfR2 become targets of tumor therapy. 15,32 ASP could inhibit the proliferation, migration, invasion, and induce apoptosis of SH-SY5Y cells. It might inactivate PI3K/Akt and JAK/STAT signaling pathways via down-regulating miR-675 in SH-SY5Y cells, thereby inhibiting the tumorigenicity of SH-SY5Y cells.…”
Section: Antitumor Activitymentioning
confidence: 97%